Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1471-4159.1998.70041662.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption by Lithium of Phosphoinositide Signalling in Cerebellar Granule Cells in Primary Culture

Abstract: Mild depolarisation (20 mM KCI) synergistically enhances the ability of a muscarinic agonist to activate phosphoinositide turnover and to elevate inositol 1,4,5‐trisphosphate [Ins(1,4,5)P3] in cerebellar granule cells in primary culture. The effects of lithium on this intense stimulation of phosphoinositide turnover was studied. Lithium causes depletion of cytoplasmic inositol and phosphoinositides, which results in the inhibition of phosphoinositide turnover within 15 min and the return of Ins(1,4,5)P3 to bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…In support of this hypothesis, lithium has previously been shown to decrease steady-state levels of PIns in neurons: these effects, however, were only seen when PIP 2 hydrolysis was hyper-stimulated for a prolonged period with the cholinergic agonist carbachol 10,11 , and this extreme pharmacological manipulation is unlikely to be relevant to normal brain function. Other studies that argue against a therapeutic role for IMPase inhibition have focussed on lithium’s effects on brain inositol and/or PIns levels.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In support of this hypothesis, lithium has previously been shown to decrease steady-state levels of PIns in neurons: these effects, however, were only seen when PIP 2 hydrolysis was hyper-stimulated for a prolonged period with the cholinergic agonist carbachol 10,11 , and this extreme pharmacological manipulation is unlikely to be relevant to normal brain function. Other studies that argue against a therapeutic role for IMPase inhibition have focussed on lithium’s effects on brain inositol and/or PIns levels.…”
Section: Introductionmentioning
confidence: 90%
“…Most previous studies of lithium’s effects in PIns synthesis used either cell lines that expressed the high capacity SMITs 29 or cerebellum granule cell neurons in which the status of SMIT-1 was not documented 10,11 ; these cells have mM levels of intracellular inositol 30,31 , which has contributed to the scepticism about inhibition of IMPase leading to inositol depletion as relevant to lithium’s therapeutic effects. Thus, a reinvestigation of the effect of lithium on inositol and PIns metabolism in primary neurons lacking SMITs is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium's inhibitory action on receptor-mediated signal-transduction pathways has been demonstrated in vitro (Atack et al 1995) showing that it reduces myoinositol levels by non-competitively inhibiting the enzyme inositol monophosphate, a catalyst for converting inositol monophosphate hydroxyls to myo-inositol (Manji et al 1996). Since the phosphoinositide cycle (PI) regulates a wide variety of neuronal functions, including intracellular calcium mobilization and protein kinase C (PKC) activity (Feldman et al 1997), lithiuminduced modification of the PI cycle has been proposed as a potential therapeutic mechanism underlying its mood-stabilizing effect (Berridge et al 1982;del Rio et al 1998;Murray and Greenberg 1997;Soares et al 1999). Although brain tissue can synthesize myo-inositol de novo , the ability of neurons to maintain a steady-state supply of cytosolic myo-inositol appears to be crucial to the resynthesis of phosphoinositides, and, conceivably, to the membrane receptor response to stimulation and neuronal homeostasis.…”
mentioning
confidence: 99%
“…It is apparent that lithium exerts an effect on intracellular second-messenger systems in which activated receptorligand complexes stimulate the turnover of inositolcontaining phospholipids (del Rio et al 1998;Feldman et al 1997;Murray and Greenberg 1997;Soares et al 1999). Lithium's inhibitory action on receptor-mediated signal-transduction pathways has been demonstrated in vitro (Atack et al 1995) showing that it reduces myoinositol levels by non-competitively inhibiting the enzyme inositol monophosphate, a catalyst for converting inositol monophosphate hydroxyls to myo-inositol (Manji et al 1996).…”
mentioning
confidence: 99%
“…Our previous investigations have also shown that lithium can decrease penile erection induced by activation of the dopaminergic system (Dehpour et al 1995;Sharifzadeh et al 1996) and yawning response induced by cholonergic activation (Sharifzadeh et al 1997). It has been reported that lithium causes depletion of cytoplasmic inositol and phosphoinositide turnover (Hallcher & Sherman 1980;Del-Rio et al 1998), which could interfere with the re-synthesis of phosphatidyl inositol bisphosphate, thus influencing the signaling mechanisms operating through the phosphoinositide system. Lithium has also been shown to attenuate protein kinase C function (Bitran et al 1995).…”
Section: Discussionmentioning
confidence: 94%